Effect of long-term weight gain on the risk of breast cancer across women's whole adulthood as well as hormone-changed menopause stages: A systematic review and dose–response meta-analysis. Issue 5 (September 2021) - Hao, Yu; Jiang, Menglu; Miao, Yunqi; Li, Xu; Hou, Can; Zhang, Xiaofan; Chen, Hui; Zhong, Xiaorong; Li, Jiayuan
Abstract: Adult weight gain is a good indicator of excess body fatness for breast cancer risk. However, little is known about the effect of weight gain during other special periods in women's lifetime. A publication search in PubMed and Embase through April 2020 was conducted. A primary meta-analysis comparing the highest and lowest category and a secondary meta-analysis based on dose–response meta-analysis were performed to calculate risk estimates with 95% confidence intervals using a random-effects model. For postmenopausal breast cancer, the relative risk for highest vs. lowest category of adult weight gain and weight gain since menopause were 1.55 and 1.59 (RR = 1.55, 95% CI: 1.40, 1.71; RR = 1.59, 95% CI: 1.23, 2.05). For per 5 kg increase in adult weight gain, the summary RR of postmenopausal breast cancer was 1.08 (RR = 1.08, 95% CI: 1.07, 1.09), which is much stronger in Asian women (RR = 1.34, 95% CI: 1.22, 1.47). There was no significant finding among premenopausal women (RR = 1.00, 95% CI: 0.83, 1.21). Same as adult weight gain, weight gain since menopause might be an equivalent predictor for postmenopausal breast cancer risk. More studies are warranted to confirm the magnitude of this association further.